PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN BERFIKIRKRITIS MATEMATIS SISWA KELAS IV DI UPT SPF SD NEGERI BAWAKARAENG 1 - Jafar, Wiknandar; Bellona Mardhatillah Sabillah; Jusmawati; Eka Fitriana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the impact of the Problem Based Learning (PBL) learning model on mathematical critical thinking skills in grade IV students in elementary schools. Critical thinking is one of the most important skills in learning mathematics, because it helps students analyze, assess, and solve problems in a logical and orderly manner. This study used an experimental method with a pre-experimental design and applied a quantitative approach. The subjects studied were grade IV C students at the UPT SPF SD Negeri Bawakaraeng 1, Makassar, with a total of 21 students. The instrument used for the study was a mathematical critical thinking ability test that had been tested and validated. The results of this data collection technique applied a pretest and posttest with 5 essay questions as a measure to assess students. The results showed a significant difference between the pretest and posttest scores of students taught with the PBL model compared to those taught using the traditional method. The pretest activity showed the frequency distribution of student scores, which showed that no students scored in the range of 85-100. A total of 8 students scored between 70-80, 10 students scored in the range of 55-69, and 3 students were in the range of 40-54. As for the posttest results, the frequency distribution showed that 12 students scored between 85-100. In addition, 9 students scored in the range of 70-84, and no students scored in the range of 55-69.